Foreign body of endodontic origin in the maxillary sinus - Marta Tanasiewicz; Anna Bubilek-Bogacz; Henryk Twardawa; Małgorzata Skucha-Nowak; Tomasz Szklarski (Elsevier, 2017)
Foreign bodies found in the maxillary sinus include tooth roots, burs, dental impression material, root-filling materials, dental implants, and needles. The purpose of this paper was to present an unusual case of a large foreign body of endodontic origin (root-filling material) removed from the maxillary sinus. A 45-year-old generally healthy male patient reported to the Department of Conservative Dentistry with Endodontics of the Medical University of Silesia, because of orbital and buccal pain on the right side of his face and headaches in the preceding 6 months. Those symptoms were associated with the end of endodontic treatment of teeth 14 and 16. Periapical X-rays, including of teeth 14 and 16, showed the presence of root canal filling with extrusion of endodontic obturation material beyond the apices of tooth 14. In the case of tooth 16, a completely filled palatal canal and incompletely filled buccal canals were found. There was also an irregular dimness at the upper edge of the X-ray image. Panoramic radiography and computed tomography demonstrated a foreign body in the right sinus. Sinus exploration was performed via a surgical procedure conducted using topical anesthesia. The root apices of tooth 14 were resected, and foreign substance was removed. The practitioner did not correctly recognize a complication that occurred during endodontic treatment, which resulted in extrusion of endodontic material beyond the root apices of tooth 14. This case emphasizes the potential impact that an involved maxillary sinus may have on endodontic therapy. Detailed diagnostic identification based on the medical interview, physical and histopathological examinations, and diagnostic imaging allowed rapid surgical intervention and prevented local and general complications. It is important to realize that the range of the periapical X-ray projection is not always sufficient. Keywords: extrusion of endodontic obturation materials, foreign body, maxillary sinus